“When a Nation Has No Leader, Poets Become Its Leaders” (Ukrainian Indigenous Literature as Viewed by Yevhen Malaniuk through a Mythological Prism) - Slonovska, Olha (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article discusses the literary-critical and national political activity of the outstanding Ukrainian poet and states figure Yevhen Malaniuk, using a corpus of his literary-critical essays. The author analyzes the oeuvre of diasporic writers in comparison with that of indigenous Ukrainian poets and prosaists who lived under the yoke of ideological prejudices and persecutions of the Soviet era, a symbiosis of “socialist realism” with stillborn “modernism”. Yearning for their homeland, Ukrainian diasporic writers created images of Ukraine the Vision, Ukraine the Dream, Ukraine the Goal, and an ideological political myth of a nation state. Yevhen Malaniuk fulfilled this philosophical and political objective brilliantly. His mythological thinking generated the concept of Ukraine the Hellas as a phenomenon of global importance. From his perspective, only by the glorious heroics of patriots and passionaries is it possible to foster national awareness. However, even with titans such as Taras Shevchenko, Bohdan Khmelnytskyi, Ivan Mazepa, and Symon Petliura, Ukrainian society was nevertheless unable to grasp such heroic endeavors adequately. Outstanding Ukrainian cultural activists never succeeded in viewing reality from a critical perspective. The poet debunks Russian colonialism and castigates Russian pro-imperial literature, the “split” Hohol, the chauvinistic propaganda of Russian culture. Yevhen Malaniuk’s oeuvre is seen as occupying a unique role in our literature